Evaluation of Air Pollution with NO2, SO2, and PM2.5 in Nasiriyah City Center, South of Iraq - Al Rukabie, Jamal S. Abd; Al-Jiboori, Monim H.; Chlaib, Hussein Kh. (Iraqi Journal of Science, 2026)
Air pollution is considered one of the most dangerous types of pollution because of the problems and risks it causes to living organisms on the surface of the Earth. This paper studied the emission of air pollutants (nitrogen dioxide, NO2, sulfur dioxide, SO2, and particulate matter PM2.5) in the city center of Nasiriyah. The data were taken from the European Mediterranean Weather Forecast (ECMWF) during the year (2022). The pollutant roses were plotted, which show the most pollutant source from the northwest direction of the electric power plant in the city and another source from the south (Nasiriyah refinery and Saba oil field). The daily rates of NO2, SO2 and PM2.5 concentrations (in µg/m3) were studied and evaluated during the four months. The Air Quality Index (AQI) was calculated and the results showed that the NO2 and SO2 categories were good while for PM2.5 was unhealthy for people with respiratory diseases and unhealthy causing the daily AQI (160 µg/m3 as the annual mean) to be high in 2022.